Password-based protection of clustered segments in distributed memory systems - Lopriore, Lanfranco (Journal of parallel and distributed computing, 2018)
With reference to a distributed system consisting of nodes connected by a local area network, we consider the problems related to the distribution, verification, review and revocation of access permissions. We propose the organization of a protection system that takes advantage of a form of protected pointer, the handle, to reference clusters of segments allocated in the same node. A handle is expressed in terms of a selector and a password. The selector specifies the segments, the password specifies an access right, read or write. Two primary passwords are associated with each cluster, corresponding to an access permission for all the segments in that cluster. A handle weakening algorithm takes advantage of a parametric one-way function to generate secondary passwords corresponding to less segments. A small set of protection primitives makes it possible to allocate and delete segments in active clusters, and to use handles to access remote segments both to read and to write. The resulting protection environment is evaluated from a number of viewpoints, which include handle forging, review and revocation, the memory costs for handle storage, the execution times for handle validation and the network traffic generated by the execution of the protection primitives. An indication of the flexibility of the handle concept is given by applying handles to the solution of a variety of protection problems. •We refer to a distributed system consisting of nodes connected by a local area network.•We consider the distribution, verification, review and revocation of access permissions.•A form of protected pointer, the handle, is used to reference clusters of memory segments allocated in the same node.•A handle referencing a given cluster includes a password and a selector of the segments in that cluster.•We take advantage of a parametric one-way function for password generation.